Case-based Clinical Reasoning Competitions: A Novel Method to Teach and Assess Clinical Reasoning Skills Among Gastroenterologists - , Anahita Sadeghi, Peyman Adibi, Fatih Oğuz Önder, Bülent Değertekin, Dilara Turan, Serhat Bor (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Sadeghi A, Adib P, Oğuz Önder F, Değertekin B, Turan D, Bor S. Case-based clinical reasoning competitions: a novel method to teach and assess clinical reasoning skills among gastroenterologists. Turk J Gastroenterol. 2024;35(10):805-807.